Leverage and Real Earning Management - Nantyah, Idzal Dwi (Universitas Dr. Soetomo, 2019)
Every firms needs capital in carrying out its business activities, this is very related to the firm's funding decisions. This funding decision raises leverage if the firms in its operations uses a source of funds that creates a fixed burden, namely debt, with the expectation of additional benefits in the form of tax savings greater than the fixed costs that must be incurred, thereby increasing firm profits. Profit becomes very important for creditors and shareholders, because profits are used as a reference used to evaluate the condition of the company. But in practice, managers take certain actions by manipulating financial statements to mislead those who have an interest in the firm, especially the firm's performance. The purpose of this study is whether leverage affects the real earnings management by using three measurements, namely Abnormal Cash Flow, Abnormal Production Cost, Abnormal Discretionary Expenses using Multiple Linear Regression. Regression results show that leverage has a significant positive effect on abnormal cash flow, leverage has a significant negative effect on abnormal discretionary expenses, leverage has a significant negative effect on abnormal production costs.